(untitled) (Caderno de Pesquisa, 2020)
The accumulation of toxic metals (e.g., cadmium) in soil and water, and consequently in the food chain, is a concern in agriculture production due to the adverse effects of these metals on food quality and crop growth, as well as the potential harm they pose to humans and other animals. The objective of this work was to assess the toxicity of cadmium (Cd) on seed germination and initial growth of thyme. The ecotoxicological effects of four Cd concentrations (15; 30; 45; and 60 mg L-1) were evaluated. The response variables were germination percentage, first count, germination speed index, total length, shoot length, root length, seedling dry mass, and tolerance index. The study found that thyme seeds exposed to 60 mg L-1 of cadmium had a lower percentage of normal plants, a 13% reduction in seed germination, and a 65% increase in abnormal plants. The Cd had an inhibitory effect on the initial growth of the seedlings by affecting the development of the roots and aerial part. It is concluded that the presence and accumulation of Cd in the cultivation substrate reduced seed germination and initial seedling growth of thyme, and that the intensity of inhibition was directly proportional to the concentration of Cd in the solutions employed.